2015
DOI: 10.1093/abbs/gmv026
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumor transforming gene: a novel therapeutic target for glioma treatment

Abstract: Glioma which has strong proliferation and angiogenesis ability is the most common and malignant primary tumor in central nervous system. Pituitary tumor transforming gene (PTTG) is found in pituitary tumor, and plays important role in cell proliferation, cell cycle, cell apoptosis, and angiogenesis. However, the role of PTTG in glioma is still incompletely investigated. Here, we explored the correlation between PTTG and glioma grade, as well as micro-vessel density (MVD). In addition, siRNA was used to silence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…MVD is an important index for the detection of tumor angiogenesis which is assessed by the immunochemistry staining of CD31. Consistent with Cui et al ( 23 ), our study revealed that the expression of CD31 was highly expressed in glioma tissues, which indicated that angiogenesis in glioma was higher than in normal brain tissues. LRIG2 expression in glioma tissues was positivity correlated with the MVD.…”
Section: Discussionsupporting
confidence: 92%
“…MVD is an important index for the detection of tumor angiogenesis which is assessed by the immunochemistry staining of CD31. Consistent with Cui et al ( 23 ), our study revealed that the expression of CD31 was highly expressed in glioma tissues, which indicated that angiogenesis in glioma was higher than in normal brain tissues. LRIG2 expression in glioma tissues was positivity correlated with the MVD.…”
Section: Discussionsupporting
confidence: 92%
“…It was demonstrated that the expression level of VEGF mRNA in patients with grade III and IV gliomas was significantly higher than that in patients with grade I and II gliomas, and the expression level of VEGF mRNA in patients with grade I and II gliomas was significantly higher than that in normal brain tissues (25)(26)(27). In addition, the cell viability, migration and invasion, and angiogenesis of gliomas may be inhibited by inhibition of the pituitary tumor transforming gene that was positively associated with the glioma grade and tumor microvessel density (28), and was considered as an important target of glioma antiangiogenic therapy. It was also demonstrated that certain angiogenic chemokines secreted by tumor cells may directly effect vascular ECs, which induces angiogenesis (29).…”
Section: Discussionmentioning
confidence: 90%
“…This gene plays important roles in cell proliferation and transformation, and the protein expressed from PTTG (securin) has been shown to be responsible for chromatid separation in mitosis 69. Studies have shown that PTTG is involved in the migration and invasion of glioma, suggesting the role of PTTG as a diagnostic and therapeutic target for glioma 70-73. Increased expression of PTTG in the tumor tissues has been found in various tumors, including glioma 71, 74, and has been shown to be related to the poor prognosis of glioma patients 71.…”
Section: Resultsmentioning
confidence: 99%